The Indirect Effects of Authentic Value and Attitude Toward Food Vlogs on the Link Between Trustworthiness and Visit Intentions: A Serial Mediation Analysis - Lacap, Jean Paolo; Moranas, Ronnie; Domasig, Kristina Paula; Rey, April Irish; Perlas, Trishia Nicole (The South East Asian Journal of Management, 2024)
Research Aims: The current study investigates how food vloggers’ trustworthiness influences viewers’ visit intention toward the featured food destination. Furthermore, it examines whether food vlogs’ authentic value and viewers’ attitudes toward food vlogs serially mediate the link between source trustworthiness and visit intentions. Design/Methodology/Approach: The respondents were identified using a purposive sampling technique. Causal-predictive research design and path modelling via partial least squares was employed to measure the hypothesised relationships. Research Findings: Source trustworthiness has a significant and positive influence on attitudes toward food vlogs and food vlog’s authentic value. Additionally, the food vlog’s authentic value was found to have a significant and positive effect on attitudes toward food vlogs and visit intention. Serial mediation also showed that food vlogs’ authentic value and attitude toward food vlogs serially mediate the relationship between source trustworthiness and visit intention. Theoretical Contribution/Originality: The findings of the study lie on the Stimulus-Organism-Response (S-O-R) paradigm by Mehrabian and Russell (1974) and illustrate the complexities associated with influencer marketing from the point of encounter with the stimulus or the food vlog, to the formulation of the intention to visit food establishments. Managerial Implications in the South East Asian Context: The study's findings underscore the significance of food vlogs in shaping consumer behaviour, particularly regarding visit intentions. Southeast Asian tourism and hospitality industries can leverage food vlogs as a tool for cultural exposure. Research Limitations & Implications: Selecting a trustworthy vlogger who has high engagement through creative and eye-catching videos is a pertinent requirement to ensure the success of a campaign to promote vlogs.